Identifikasi Karakteristik Fisik Berbagai Jenis Agregat Halus dan Korelasinya pada Sifat Beton Segar dan Beton Padat - N.N. Kencanawati; S. Rawiana; A. Rofaida; N.A. Febriyanti (Civil Engineering Department, Tadulako University, 2023)
One of the main constituents of concrete is fine aggregate or sand. As a filler, the characteristics of sand affect the properties of both fresh and hardened concrete. The aim of this research is to identify the characteristics of various types of sand and to correlate them with the properties of the concrete. The type of sand used in the experiment is common type of sand used in construction; for instance, silt sand, river sand, and beach sand, as well as recycled sand from concrete waste. The examination on physical characteristics includes visualization with a digital microscope, specific gravity, water absorption, fine modulus, and impurities content. This characteristic is compared with the value of slump, concrete unit weight, and concrete compressive strength. Quarry sand has denser particles and a fairly coarse texture, while recycled sand has the finest, hollowest, lightest particles and a lighter color than other sands. According to the properties of fresh concrete, silt sand produces the lowest slump value while recycled sand has the highest slump value. A positive correlation in the form of y = 1,55x + C is obtained from the relationship of the specific gravity of sand (x) to the compressive strength of concrete (y) and constants (C). the same correlation but in a negative relationship is obtained from the influence of water absorption characteristics